Meningkatkan Keterampilan Menyimak Melalui Media Film Kartun Siswa Kelas VIII MTs DDI Kalukuang Kota Makassar - Andi, Andi; Jumriati, Jumriati; Erniati, Erniati; Supriadi, Supriadi; Arief S, Herawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
This research aims to determine the improvement of listening skills through cartoon film media for class VIII students at MTs DDI Kalukuang. The approach used in this research is Classroom Action Research. This research focuses on problems related to listening skills using cartoon film media. The data obtained was carried out in two cycles, namely cycle I and cycle II with stages of planning, implementation, observation and reflection. The subjects of this research were class VIII students at MTs DDI Kalukuang Makassa, totaling 23 students consisting of 8 male students and 15 female students. The data collection technique uses observation to assess students' listening skills and the results of students' writing abilities, and the results of their listening skills and documentation of students' work results, while the criteria for success are in terms of the results achieved in class VIII MTs DDI Kalukuang in this study are the average scores. The average listening skills of students increased from cycle I to cycle II reaching 75 from the number of students who got a score of > 75 (KKM Listening Skills). The results of the research show that students' listening skills by paying attention to the average value of the aspects of assessing effectiveness in paying attention to explanation are sufficient, students' ability to understand the material presented by the teacher is sufficient, attitudes in receiving learning material are sufficient, students' concentration resistance is adequate, and the results of the research cycle I reached 66 and in cycle II it increased to 80 and had met the minimum completeness criteria (KKM) standards targeted by researchers